The Generic Competencies of Vocational Teachers: the Situation and the Demand in Labour Market - Pečiulauskienė, Palmira (Acta Paedagogica Vilnensia, 2007)
The promoting of the generic competencies of the vocational teachers is a relevant issue in information society. The generic competencies providing the opportunity of working in various areas makes them significant in theory and practise of vocational training. From the point of the development of these competencies more and more attention is paid towards the functional learning conception involving the competency of planning, the organizational competency, the methodical competency, the competency of continuous learning. The authorities of the vocational training institutions have evaluated the need of these competencies. The data of research shows that the competency of planning as well as methodical competency is of significant importance. The authorities of the vocational training institutions have also evaluated the teachers’ possessions of the distinguished competencies. The vocational teachers’ competency of planning is claimed to be at the high level while the competency of continuous learning and methodical competency is at a low level. Consequently, the inconsistency of the need of the competencies and the possession of the competencies is observed. The competency of continuous learning has some exclusive features. The need of this competency is of great importance whereas the possession of it is relatively small. Furthermore, from the aspect of the respondents’ education and gender the significantly important differences are observed in the attitude towards the competency of continuous learning. The authorities of the vocational institutions have a different attitude towards this competency depending on their age. The competency of continuous learning is treated as important or very important by all respondents (age between 20 and 61). However, the major part (62.5 proc.) of respondents aged between 41 and 50 years have indicated this competency as very important while the elder respondents (of age more that 51 years) have graded it only as important. It is worth mentioning that this percentage difference has not been approved as being of statistical importance.